Pengaruh Sudut Kemiringan dan Suhu Nozzle terhadap Kekasaran Permukaan pada Bagian Overhang Hasil Cetak 3D Material PLA - M. Fendy Kussuma Hadi Sufyan; Ikhwan Taufik; Silviana Silviana; Gito Sugiyanto (CV. IRA PUBLISHING, 2025)
This study aims to investigate the influence of overhang inclination angle and nozzle temperature on the surface roughness of the overhang section in a 3D printed object using Polylactic Acid (PLA) material with the Fused Deposition Modeling (FDM) method. An experimental approach was employed by varying the overhang angles (35˚, 45˚, and 55˚) and nozzle temperatures (210˚C, 220˚C, and 230˚C) during the printing process. Surface roughness measurements were performed on unsupported overhang areas using a surface roughness tester. The results showed that surface roughness increased with greater overhang angles and higher nozzle temperatures. The lowest surface roughness value was recorded at 210˚C with a 35˚ overhang angle, while the highest was observed at 230˚C with a 55˚ overhang angle. These findings indicate that controlling the nozzle temperature and overhang angle is crucial for achieving optimal surface quality in overhang printing. This study is expected to contribute to the optimization of FDM process parameters to produce smoother surfaces.